Smoking counts: experience of implementing questions on smoking on official death certification systems. (20th November 2018) - Sitas, Freddy; Bradshaw, Debbie; Egger, Sam; Jiang, Guohong; Peto, Richard
Abstract: We describe our experience in several settings, following a suggestion in 1983 to add questions on the smoking status of the deceased on the UK death certificate as an effective way to monitor the evolution of the smoking epidemic. In South Africa in 1997 and in Tianjin Municipality, China, in 2010, questions about the smoking habits of the deceased were inserted on the official death certificates. In both places a system now exists to routinely collect information on smoking status in relation to causes of death. Results from two million South African and 300 000 Chinese deceased individuals have been reported, and the sample size in both places continues to grow. An unsuccessful attempt was made in 2008 to insert smoking questions on the Australian death notification forms but comments and concerns from the registrars of births, marriages and deaths have international applicability. In both China and South Africa, inserting questions on smoking on the death notification forms was not a trivial task—in each it required, as a minimum, significant commitment from several government agencies. Benefits, however, include a better local understanding of the smoking epidemic and allowing for planning and monitoring of tobacco control programmes. Documenting the varied experiences of collecting information on smoking on death notification forms is useful to those wishing to introduce such questions in their own settings. This is pertinent especially at a time when vital registration systems are being improved, with an aim to monitoring sustainable development goals.